Late Miocene hominin teeth from the Gona Paleoanthropological Research Project area, Afar, Ethiopia. - Simpson, Scott W; Kleinsasser, Lynnette; Quade, Jay; Levin, Naomi E; McIntosh, William C; Dunbar, Nelia; Semaw, Sileshi; Rogers, Michael J (Journal of Human Evolution, 2015)
Since 2000, significant collections of Latest Miocene hominin fossils have been recovered from Chad, Kenya, and Ethiopia. These fossils have provided a better understanding of earliest hominin biology and context. Here, we describe five hominin teeth from two periods (ca. 5.4 Million-years-ago and ca. 6.3 Ma) that were recovered from the Adu-Asa Formation in the Gona Paleoanthropological Research Project area in the Afar, Ethiopia that we assign to either Hominina, gen. et sp. indet. or Ardipithecus kadabba. These specimens are compared with extant African ape and other Latest Miocene and Early Pliocene hominin teeth. The derived morphology of the large, non-sectorial maxillary canine and mandibular third premolar links them with later hominins and they are phenetically distinguishable and thus phyletically distinct from extant apes. Copyright © 2014 Elsevier Ltd. All rights reserved.
22 citations (Crossref) [2023-10-31] Place: England Simpson, Scott W. Department of Anatomy, Case Western Reserve University School of Medicine, Cleveland, OH 44106-4930, USA; Institute for the Science of Origins, Case Western Reserve University, Cleveland, OH 44106, USA; Laboratory of Physical Anthropology, Cleveland Museum of Natural History, Cleveland, OH 44106, USA. Electronic address: sws3@cwru.edu. Kleinsasser, Lynnette. Department of Geosciences, University of Arizona, Tucson, AZ 85721, USA; Barrick Cortez, HC 66 Box 1250, Crescent Valley, NV 89821 USA. Electronic address: lkleinsasser@barrick.com. Quade, Jay. Department of Geosciences, University of Arizona, Tucson, AZ 85721, USA. Electronic address: quadej@email.arizona.edu. Levin, Naomi E. Department of Earth & Planetary Sciences, Johns Hopkins University, Baltimore, MD 21218, USA. Electronic address: nlevin3@jhu.edu. McIntosh, William C. New Mexico Bureau of Geology and Mineral Resources & Department of Environmental Science, New Mexico Institute of Mining and Technology, Socorro, NM 87801, USA. Electronic address: mcintosh@nmt.edu. Dunbar, Nelia. Department of Environmental Science, New Mexico Institute of Mining and Technology, Socorro, NM 87801, USA. Electronic address: nelia@nmt.edu. Semaw, Sileshi. Centro Nacional de Investigacion sobre la Evolucion Humana (CENIEH), Paseo Sierro de Atapuerca 3, Burgos 09002, Spain; The Stone Age Institute, 1392 West Dittemore Road, Gosport, IN 47433, USA; CRAFT, Indiana University, Bloomington, IN 47405, USA. Electronic address: Sileshi.semaw@cenieh.es. Rogers, Michael J. Department of Anthropology, Southern Connecticut State University, New Haven, CT 06515, USA. Electronic address: rogersm1@southernct.edu.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Tooth/ah [Anatomy & Histology]; Afar; Animals; Ardipithecus; Ardipithecus kadabba; Ardipithecus ramidus; Biological Evolution; Ethiopia; Fossils; Hominidae; Hominina; Late miocene; Miocene; Orrorin; Tooth; Western ethiopian escarpment; anatomy and histology; animal; anthropology; canid; dept.ant; evolution; fossil; hominid; morphology; peer-reviewed; tooth